ANALISIS KAPASITAS TAMPUNGAN EMBUNG SERBAGUNA KALEPADANG UNTUK MEMENUHI KEBUTUHAN AIR BAKU PENDUDUK KECAMATAN BONTOHARU - Tambaru, Tambaru (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2024)
The problem of the availability of raw water is also faced by residents in the Bontoharu District, Selayar Islands Regency. Even though the area has adequate water sources (surface water, river water, underground water, and springs), the problem is how to optimally capture and distribute water from these water sources so that it can be used by residents. Facilities and infrastructure in the raw water supply system such as broncaptering, public service tanks, and pressure relief tanks need to be designed and built so that people can meet their water needs without having to bother taking it directly to water sources which are sometimes very difficult to reach. In preparing the Design Review for the Development of the Kalepadang Multipurpose Reservoir, Kec. Bontoharu. This Methodology of Work Implementation is Preliminary Survey and Investigation, Data Collection, Hydrological Analysis, Reservoir Construction Planning, and Reservoir Construction Stability. Budget Plan. Activities carried out to achieve the goal of community service include an Analysis of the Capacity of a Multipurpose Reservoir as a Reference for the Development of Standard Water Infrastructure to Meet the Water Needs of the Local Population Masalah ketersediaan air baku ini juga dihadapi oleh penduduk di wilayah Kecamatan Bontoharu Kabupaten Kepulauan Selayar. Meskipun wilayah tersebut memiliki sumber air (air permukaan, air sungai, air bawah tanah dan mata air) yang cukup memadai, namun yang menjadi kendala adalah bagaimana cara menangkap dan menyalurkan air dari sumber air tersebut secara optimal sehingga dapat dimanfaatkan oleh penduduk. Sarana dan prasarana dalam sistem penyediaan air baku seperti broncaptering, bak pelayanan umum dan bak pelepas tekan yang perlu didesain dan dibangun agar masyarakat dapat memenuhi kebutuhan air tanpa harus bersusah payah mengambil langsung ke sumber air yang terkadang sangat sulit dijangkau. Dalam penyusunan Review Desain Pembangunan Embung Serbaguna Kalepadang Kec. Bontoharu. ini Metodologi Pelaksanaan Pekerjaan adalah Survey dan investigasi pendahuluan, Pengumpulan data, Analisis hidrologi, Perencanaan konstruksi embung, Stabilitas konstruksi embung dam Rancangan Anggaran Biaya. Kegiatan yang dilakukan untuk mencapai tujuan pengabdian kepada masyarakat melakukan Analisis Kapasitas Tampungan Embung Serbaguna Sebagai Acuan Pembangunan Prasarana Air Baku Untuk Memenuhi Kebutuhan Air Penduduk Setempat.